The Scarlet Letter - Hawthorne, Nathaniel, 1804-1864. (Chagrin Falls, Ohio : Findaway World, 2006)
Nathaniel Hawthorne's classic novel "The Scarlet Letter" about an adulteress, Hester Prynne, and the scorn she receives from the people in her Puritan New England village.